Automatic positioning device of pipe insertion machine - YI KANGFENG; CHENG JINPING; ZHANG JUN; WANG FALI (2014)
The utility model relates to an automatic positioning device of a pipe insertion machine, and belongs to the field of machines. The automatic positioning device comprises a rotating disc, wherein a sleeve is arranged above the rotating disc; a mechanical hand is arranged just above the sleeve. The automatic positioning device is characterized in that the upper port of the sleeve is provided with an upper infrared detection device, and the lower port of the sleeve is provided with a lower infrared detection device. According to the automatic positioning device, a triggering metal sheet is arranged on the positioning position of the rotating disc, and an insertion pipe triggering infrared detection device is arranged above the rotating disc, so that the accuracy for positioning is achieved.